2019
DOI: 10.1590/2177-6709.24.2.066-072.oar
|View full text |Cite
|
Sign up to set email alerts
|

Lubricating conditions: effects on friction between orthodontic brackets and archwires with different cross-sections

Abstract: Objective: This study investigated the effect of the condition of lubrication on the friction between brackets and NiTi archwires of different rounded cross-sections. Methods: Brackets (Roth, GAC) were affixed to a device connected to a universal testing machine into which segments of archwire were placed (NiTi, Nitinol, GAC) with cross-sections of 0.012-in, 0.016-in and 0.020-in. Once the wire was in the bracket slot, the following lubricants were applied: human saliva (HS: positive control), distilled wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…[31] e ligating method for self-ligating brackets occurs without the need for elastic or metal ligature but through clips or doors present in the brackets which, when closed, provide the sliding of the round section wire with minimal or no interaction to the linkage system. [2,6,24,32,33] In the current study, passive and active self-ligating brackets showed no statistically significant differences when using a 0.018"gauge steel wire, regardless of whether the elastomeric chain is used or not, corroborating with studies in which passive and active self-ligating brackets showed low or no resistance to friction in round section wires. [13,17,25,27,32] Depending on the gauge, section, and position of the wire in the slot, the clips of the active brackets work passively, without interaction with the wire, similar to the doors of the passive self-ligating brackets, showing similar friction results.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…[31] e ligating method for self-ligating brackets occurs without the need for elastic or metal ligature but through clips or doors present in the brackets which, when closed, provide the sliding of the round section wire with minimal or no interaction to the linkage system. [2,6,24,32,33] In the current study, passive and active self-ligating brackets showed no statistically significant differences when using a 0.018"gauge steel wire, regardless of whether the elastomeric chain is used or not, corroborating with studies in which passive and active self-ligating brackets showed low or no resistance to friction in round section wires. [13,17,25,27,32] Depending on the gauge, section, and position of the wire in the slot, the clips of the active brackets work passively, without interaction with the wire, similar to the doors of the passive self-ligating brackets, showing similar friction results.…”
Section: Resultssupporting
confidence: 87%
“…In this case, even with the difference between the closing system of passive and active brackets, when using elastomeric chains over the bracket/wire set, the elastomeric chain comes into contact with the wire, causing greater friction during sliding, and regardless of the wire. [5,6,12,17,25] In all situations tested in this study, the resistance to friction was significantly higher with the use of the 0.019" × 0.025" wire. ese results can be explained by the decreased area inside the slot of the bracket in the rectangular 0.019" × 0.025" wires, as they are larger in the vertical direction when compared to the round 0.018" wires, causing greater friction due to the increased surface contact of the wire corners with the inner walls of the bracket slot.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The literature reinforces the need for a deeper assessment with CuNiti wires 1 , controlling the in vitro testing environment, as a dry environment may promote higher sliding and frictional resistance when assessing different orthodontic wires 16 . The importance of controlling variables such as environment and temperature during in vitro tests becomes evident for assessing the correlation of surface roughness and frictional resistance of the different bracket-wire systems.…”
Section: Introductionmentioning
confidence: 69%
“…[2] Friction is affected by biological factor-such as saliva, debris, and biodegradation of the appliance's components that has been used-and physical factor as the using of brackets, archwires, and ligations. [3] The shape, size, and structures of the fixed appliances' components will affect the treatment result. [4] The generated forces of bracket and archwire interactions can be measured from its surface roughness.…”
Section: Introductionmentioning
confidence: 99%